Mindfulness-Based Interventions and Endurance Performance Under Pressure : A Systematic Review - Billa , Angel Salsa; Agustina , Amelia; Awalludin, Muchammad Rizky; Dika, Astia; Iwana , Azzahrah Shafira; Ridlowi , Dhani Achmad; Yulianti , Diah Ayu Tri; Yani , Eli Dwi; Ningsih , Etiya Mulya; Almutairi, Reem Iafi (Tarqabin Nusantara Group, 2024)
Mindfulness-based interventions (MBIs) have gained attention for their potential to enhance athletic performance, particularly under pressure. These interventions are thought to improve psychological and physiological factors, including stress reduction, attention regulation, and endurance capacity, which are critical for maintaining performance in high-pressure situations. A systematic review was conducted following PRISMA guidelines to synthesize evidence on the impact of MBIs on endurance performance under pressure. Studies were identified through a comprehensive search of academic databases and evaluated using predefined inclusion and exclusion criteria. Key findings indicate that MBIs significantly reduce anxiety and stress, enhance mental attributes such as focus and emotion regulation, and improve endurance performance metrics. Neurocognitive benefits, such as improved executive functions and reduced negative ruminations, were also reported. This review concludes that MBIs are promising tools for optimizing athletic performance. Future research should focus on standardizing interventions and exploring their long-term effects across diverse athletic contexts.